Peran Mediator Kekuatan Brand Ambasador terhadap Hubungan antara Resonances Merk dan Word of Mouth pada Keputusan Pemilihan Produk Lending di Bank Negara Indonesia Cabang Ende - Mohamad Nur H. Abdul Azis; Mansyur Abdul Hamid; Avianita Rachmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Marketing communication strategies using brand ambassadors are often applied by companies in promoting products that will be marketed to consumers so that they are right in making decisions. Brand Resonances can change the behavior caused by brand loyalty such as repeat purchases and participating in activities held by the company’s brand. Usually consumers before making a purchase will look for information about a product so that word of mouth can also be a powerful source information in influencing consumer purchasing decisions. Banks need a holistic and systematic strategy to reimagine and reinvent their business around digital technology competencies to emerge as a truly digital entity.